Kepentingan Publik dan Kualitas Pendidikan di Era Otonomi Daerah - Satija Satija (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2004)
The decision of the Indonesian Law Makers to approve the bill of the National Education System (Undang-Undang Sistem Pendidikan National) to become the law is one of the important agendas in the Indonesian education rystem. Besides produced positive impacts, the implementation of this law, unfortunately, has also caused a lot of controversies in the community. One of them was the disparity of the amount of the budget spent by the localgovernments allocated in the education activities. Paying special attention on the negative impacts of the implementation of National Education System, the author suggests that the efforts to improve the quality of Indonesian education should not be done partially, but simultaneously accross the nation.